(untitled) (KELAJAK SARI YANGI O’ZBEKISTON: ILM-FAN, TEXNOLOGIYA VA TA’LIM, 2025)
This thesis analyzes how artificial intelligence (AI) contributes to improving the export capacity and competitiveness of Uzbekistan’s apparel industry. Using global evidence and Uzbekistan’s digital modernization trajectory (2017–2025), the paper demonstrates how AI tools in design, supply chain management, quality control, forecasting, and digital marketing increase efficiency, reduce costs, and strengthen integration into international value chains. The study concludes that structured AI adoption, paired with workforce training and government support programs, can significantly accelerate apparel export growth.